High Voltage Resistive Divider Based on Cast Microwire in Glass Insulation on 6–24 kV Alternating Current of Commercial Frequency. - Juravleov A.; Sit M.; Colpacovich I.; Cojocaru D.; Cleimenov V. (Problems of the Regional Energetics, 2008)
It is presented the analysis and description of the construction of the high voltage resistive divider on the base of cast microwire in glass insulation on 6–24 kV alternating current of commercial frequency. It is presented the procedure of compensation of frequency error during the process of fabrication of divides and results of tests of the sample model of the divider as well.